Peninggalan Kolonial Di Kemukiman Saree Kecamatan Lembah Seulawah, Aceh Besar, dan pemetaan potensi wisatanya - Oktaviana, Dina; Rizky, Sarvina Fitri; Agustina, Sylvia; Yusuf, Myna Agustina (Universitas Syiah Kuala, 2024)
The discovery of a former railroad track that connects Padang Tiji (Pidie) to Gampong Lamtamot (Aceh Besar) is an evidence of the arrival of the invaders, the Dutch colonialists, who colonize Aceh Besar Regency. Various buildings and infrastructure were made to support their existing which several of those are still physically exist in the Saree Settlement, Lembah Seulawah District, in the forms of chimneys, houses, wells, ponds, old dams, and water distribution tanks. They are abandoned but hold the potential as a historical tourist spot in relation to the spirit of the people of the Aceh Besar Region who have fought against the colonial for Indonesian independence. This research is conducted to map each heritage in the Saree Settlement and explore the tourism potential of each heritage by examinging the strengths and the weaknesses as well as the opportunities and challenges formed by these strengths and weaknesses. The data collected are the result of direct observation, interviews, and lierature review. The results showed that there are buildings that are not well maintained and there are also some buildings that have been managed as tourist attractions which each of them holds the potential of either educational potential (research centers, study tour objects), natural potential (recreation), man-made, and cultural potential (tourist attractions). Furthermore, this study also adresses the parties that can support the implementation of the potential in order to to maintain the local wisdom and improve to economic of the surrounding community of this heritage.